PKM PENGEMBANGAN PRODUK LOKAL SINGKONG MENJADI KERIPIK SINGKONG RASA BALADO KHAS DESA PETANANG PROGRAM MBKM KKN TEMATIK - Sari, Desti Rahma; Shellamitha, Dinda; Pratama, Yopan; Hertati, Lesi; Hendarmin, Rum; Syafri, Lili; Munandar, Aris (Transpublika Publisher, 2022)
Petanang Village is located in the Muara Enim Regency of South Sumatra Province. It is one of the communities in the Lembak District. The land around Petanang Village is suitable for the cultivation of cassava plants. Producing goods that have been processed is one way to make the most of this potential. At the moment, numerous processed products made from the primary ingredient of cassava are available in Petanang Village. These items include chips, sweet potato crackers, and class. In this PKM activity, we want to develop local products from the Petanang village by going through several stages, the first stage being the preparation and survey stage, the second stage being the implementation stage, and finally the evaluation stage of some of these stages, we decided to make cassava chips because in this Petanang village, no one has sold them because cassava chips are easily tough, which is why we want to develop cassava chips that are crispy and not tough.